The investigation on daytime conjugate hemispheric asymmetry along 100°E longitude using observations and model simulations: New insights. Issue 10 (15th May 2022) - Kalita, B.R.; Bhuyan, P.K.; Nath, S.J.; Choudhury, M.C.; Chakrabarty, D.; Wang, K.; Hozumi, K.; Supnithi, P.; Komolmis, T.; Yatini, C.Y.; Le Huy, M.
Abstract: The hemispherical asymmetry of the low latitude region along 100°E ± 5°E is scrutinized for the year 2015 at magnetically conjugate points on seasonal and intra-seasonal time scales. Two conjugate Ionosonde station pairs are selected- one pair in the inner valley (from SEALION) and the other in the outer edges of the EIA region. The anomaly in the stations is estimated using the difference of low latitude NmF2 from the dip equatorial NmF2 in the same meridian. A monthly average scheme is used instead of a seasonal mean, as the month-to-month variations are found to provide intricate details. The anomaly at the conjugate stations is highly asymmetric even during the equinoctial months of March and October, whereas it is nearly symmetric during April. During June/July, the morning time hemispheric asymmetry (larger on the winter side) temporarily reduces in the midday period and then reverses sign (larger in summer) in the afternoon. The NmF2 observations suggest a close relation of hemispheric symmetry to the position of the subsolar point with respect to the dip equator and a shift/expansion of the trough region of the EIA towards the summer hemisphere. The inter-hemispheric comparison of the hmF2 suggests a strong modulating influence of meridional winds at both the inner and outer stations which depend strongly on the relative position of the subsolar point with respect to the field line geometry. Theoretical (SAMI3/SAMI2) and empirical model (IRI) simulations show a meridional movement of the EIA region with the subsolar point. The winter to summer hemisphere movement of the EIA trough and crest region is also reproduced in the GIM-TEC along 100°E for 2015. This shifting or tailoring of the trough and the crest region is attributed primarily to the meridional wind field, which varies with the shifting position of subsolar point relative to the field line geometry. The seasonal and intra-seasonal difference in the NmF2 hemispheric asymmetry is attributed to the misalignment of the two centers of power viz., the thermospheric/neutral processes and the electromagnetic forces, due to the geographic-geomagnetic offset in this longitude.